Lost between languages and symptoms: multilingual communication breakdowns and patient safety in Indonesian emergency care - Noni Fidya Ayu Anandasari (CV Narasi Khatulistiwa Indonesia, 2026)
Background: Multilingual emergency care in Indonesia operates at the intersection of clinical urgency, regional language diversity, and patient-safety demands, where symptoms must be transformed rapidly into actionable diagnostic and triage information. Objective: This study examines how multilingual communication breakdowns are represented and how they become safety-relevant across Indonesian emergency-care discourse. Method: Using a qualitative corpus-based discourse-pragmatic design, this study analyzed 22 publicly verifiable documents, including Indonesian regulations, Ministry materials, national clinical-communication studies, emergency-language access research, and global patient-safety frameworks. Results: Findings show that communication risk is most visibly institutionalized through governance language, yet multilingual procedures remain under-specified in relation to dialect, interpreter access, family mediation, and patient-understandable explanation. Interactional analysis indicates that breakdowns cluster around symptom elicitation, consent, discharge instruction, documentation, and mediation, suggesting that misunderstanding emerges across care transitions rather than at a single conversational point. Implication: Safety-linkage analysis further shows that diagnostic uncertainty, triage prioritization, documentation continuity, disclosure, and institutional readiness are the main pathways through which linguistic ambiguity may become patient-safety vulnerability. Novelty: By integrating medical linguistics, discourse pragmatics, and diagnostic-safety analysis, this study reframes language access as emergency-care infrastructure and offers a cautious model for examining multilingual risk without claiming unsupported causality for future empirical work in multilingual, high-pressure clinical research settings.